2012
DOI: 10.1620/tjem.228.163
|View full text |Cite
|
Sign up to set email alerts
|

Flare Phenomenon Following Gefitinib Treatment of Lung Adenocarcinoma with Bone Metastasis

Abstract: The skeleton is the most common site for distant metastasis in patients with cancer. To detect bone metastasis and evaluate the efficacy of treatment, we usually use bone scintigraphy and check serum alkaline phosphatase (ALP). However, such evaluation is sometimes difficult due to flare phenomenon. A 61-year-old male was referred to our department with a suspected diagnosis of lung cancer. Following thorough examinations, he was diagnosed with primary lung cancer (adenocarcinoma, Stage IV) and found to have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…[6] Our patient demonstrated a rapid improvement of bone pain and tumor regression by gefitinib. This study might support the previous report by Arai et al [3] suggesting a favorable response to EGFR-TKI in case of ALP flare. It is of interest that Shimazaki et al [8] first observed ALP flare-like phenomenon in a patient with multiple myeloma who received bortezomib for recurrent massive bone lesions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…[6] Our patient demonstrated a rapid improvement of bone pain and tumor regression by gefitinib. This study might support the previous report by Arai et al [3] suggesting a favorable response to EGFR-TKI in case of ALP flare. It is of interest that Shimazaki et al [8] first observed ALP flare-like phenomenon in a patient with multiple myeloma who received bortezomib for recurrent massive bone lesions.…”
Section: Discussionsupporting
confidence: 93%
“…[1] It is generally accepted that ALP flare emerges when systemic treatment is effective, since osteosclerotic change of the osteolytic lesion is seen radiographically. [2,3] Although osteosclerosis without ALP flare has been well documented, [4,5] ALP flare is reported to occur in only 5% of non-small cell lung cancer (NSCLC) patients treated with epidermal growth factor tyrosine kinase inhibitor (EGFR-TKI). [6] Since the frequency is relatively low, precise characteristics of ALP flare in NSCLC have not yet been elucidated, but it seems important not to misinterpret ALP flare as a progression of bone lesion.…”
Section: Introductionmentioning
confidence: 99%
“…In NSCLC, different case series on transient increased bone 18F-FDG uptake during chemotherapy [9,10] indicating initial response to anticancer treatment rather than a treatment failure, have been reported. Similar findings have also been described with 18F-FDG-PET/CT [11] and 99mTc-Bone Scintigraphy during EGFR TKIs (Table 1) [12,13]. On the contrary, osteoblastic reaction/response consists in the appearance of either new osteoblastic lesions or of a sclerotic component within or around lytic lesions at CT imaging.…”
supporting
confidence: 84%
“…A possible mechanism for the 'flare' pheno menon is the osteoblastic healing of the bone metastases (14), which has been demonstrated by Messiou et al (11) and Hashisako et al (15). This mechanism may also explain the 'flare' phenomenon on CT, which is capable of differentiating osteoblastic alterations by itself (5).…”
Section: Discussionmentioning
confidence: 98%